1994
DOI: 10.2105/ajph.84.8.1265
|View full text |Cite
|
Sign up to set email alerts
|

The burden and outcomes associated with dehydration among US elderly, 1991.

Abstract: OBJECTIVES. Dehydration has been underappreciated as a cause of hospitalization and increased hospital-associated mortality in older people. This study used national data to analyze the burden and outcomes following hospitalizations with dehydration in the elderly. METHODS. Data from 1991 Medicare files were used to calculate rates of hospitalization with dehydration, to examine demographic characteristics and concomitant diagnoses associated with dehydration, and to analyze the contribution of dehydration to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
126
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(141 citation statements)
references
References 12 publications
6
126
1
1
Order By: Relevance
“…Dehydration in older adults has been shown to be a reliable predictor of increasing frailty, progressive deterioration in cognitive function and an overall reduction in quality of life (Warren et al, 1994;Miller et al, 1998). These adverse long-term outcomes of dehydration in the elderly mandate further research into the pathophysiology and manifestations of mild dehydration in order to facilitate early recognition and prompt intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Dehydration in older adults has been shown to be a reliable predictor of increasing frailty, progressive deterioration in cognitive function and an overall reduction in quality of life (Warren et al, 1994;Miller et al, 1998). These adverse long-term outcomes of dehydration in the elderly mandate further research into the pathophysiology and manifestations of mild dehydration in order to facilitate early recognition and prompt intervention.…”
Section: Introductionmentioning
confidence: 99%
“…This population is at risk for dehydration because the elderly have a diminished sensation of thirst and are less able to regulate their¯uid balance (Crowe et al, 1987;Phillips et al, 1991). If left untreated, dehydration can result in death in many cases (Mahowald & Himmelstein, 1981;Warren et al, 1994). Dehydration is poorly de®ned and its clinical signs can be vague, especially in the elderly (Chernoff, 1994;Weinberg & Minaker, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study from 50 sites in Europe [7] found that 75% of study participants with mild COPD (GOLD stage II) were already taking inhaled corticosteroids, despite the fact that no inhaled medication has been found to improve clinical outcomes in patients with an FEV1 .50% pred [8].…”
Section: To the Editorsmentioning
confidence: 99%
“…This may be due to the fact that chronic renal impairment is more prevalent in the older population, and dehydration, which is common in acutely unwell older patients, may also contribute to a higher urea level [8]. With this background, we set out to assess whether raising the cut-off point of urea, while keeping the other criteria in CURB-65 as they are, would improve the specificity and positive predictive value (PPV) of the criteria in predicting mortality.…”
mentioning
confidence: 99%